What Feeds the Benthos in the Arctic Basins? Assembling a Carbon Budget for the Deep Arctic Ocean - Wiedmann, Ingrid; Ershova, Elizaveta; Bluhm, Bodil Annikki; Nöthig, Eva-Maria; Gradinger, Rolf R.; Kosobokova, Ksenia; Boetius, Antje (Frontiers in Marine Science, 2020)
Half of the Arctic Ocean is deep sea (> 1000 m), and this area is currently transitioning from being permanently ice-covered to being seasonally ice-free. Despite these drastic changes, it remains unclear how organisms are distributed in the deep Arctic basins, and particularly what feeds them. Here, we summarize data on auto- and heterotrophic organisms in the benthic, pelagic, and sympagic realm of the Arctic Ocean basins from the past three decades and put together an organic carbon budget for this region. Based on the budget, we investigate whether our current understanding of primary and secondary production and vertical carbon flux are balanced by the current estimates of the carbon demand by deep-sea benthos. At first glance, our budget identifies a mismatch between the carbon supply by primary production (3-46 g C m-2 yr-1), the carbon demand of organisms living in the pelagic (7-17 g C m-2) and the benthic realm (< 5 g C m-2 yr-1) versus the low vertical carbon export (at 200 m: 0.1-1.5 g C m-2 yr-1, at 3000-4000 m: 0.01-0.73 g C m-2 yr-1). To close the budget, we suggest that episodic events of large, fast sinking ice algae aggregates, export of dead zooplankton, as well as large food falls need to be quantified and included. This work emphasizes the clear need for a better understanding of the quantity, phenology, and the regionality of carbon supply and demand in the deep Arctic basins, which will allow us to evaluate how the ecosystem may change in the future.